American Colony in Jerusalem collection - American Colony (Jerusalem); Spafford, Anna T., 1842-1923.; Spafford, Horatio Gates, 1828-1888.; Vester, Bertha Spafford, 1878-1968.
Correspondence, diaries, minutes, notes, hymns, financial and legal records, scrapbooks, printed matter, photographs, photograph albums, and other papers relating to the history of the American Colony and its members, particularly the Spafford, Vester, and Whiting families. Documents the events that led to the founding of this cooperative Christian community in the Holy Land; the lives and philanthropic work of American Colony members including the Anna Baby Home (later the Anna Spafford Baby Home, the Spafford Children's Hospital, and Spafford Children's Center) and other health care services; the secularization and shift toward incorporation of the religious commune; tourist services provided by the colony; and the conflict and split between American and Swedish members. Also documents life in Jerusalem and Palestine as part of the Ottoman Empire, the British mandate, Jordan, and Israel.
Documents business interests including the American Colony Stores and Fr. Vester & Co. Subjects also include the trial in Chicago concerning Mary Whiting's custody of her two children, John D. Whiting and Ruth Whiting; Swedes emigrating to join the American Colony; the locust plague of 1915; antagonism of the U.S. consuls toward the colony; World War I in Palestine; the 1927 earthquake; and Jewish-Arab violence especially the Israel-Arab War, 1948-1949. Includes the papers of Anna T. Spafford, Horatio Gates Spafford, and Bertha Spafford Vester. Horatio Gates Spafford's papers include his handwritten lyrics to the hymn, It is well with my soul, written after a shipwreck that resulted in the death of his four daughters. Other individuals represented include Anna Grace Vester, Frederick Vester, Frieda Vester, Horatio Vester, John Vester, Louise Vester, Tanetta Vester, Valentine Vester, Grace Spafford Whiting, and John D. Whiting.
Selected material also available through the Library of Congress Web site.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Religious community in Jerusalem founded by American emigré Christians, Horatio Gates Spafford and his wife, Anna T. Spafford, and perpetuated by their daughter, Bertha Spafford Vester, and others.
Collection material chiefly in English, with Arabic, Hebrew, Swedish, and Turkish.
Keywords: Vester, Anna Grace; Vester, Frederick; Vester, Frieda; Vester, John; Vester, Louise; Vester, Tanetta; Vester, Valentine; Whiting, Grace Spafford; Whiting, Mary; Whiting, Ruth; Whiting, John D. -- 1882-1951.; Spafford family; Vester family; Whiting family; American Colony Stores; Anna Baby Home; Anna Spafford Baby Home; Fr. Vester & Co; Spafford Children's Center; Spafford Children's Hospital; Americans -- Palestine; Charities -- Palestine; Christian communities -- Palestine; Consuls -- Jerusalem; Consuls -- Palestine; Earthquakes -- Palestine; Hymns; Israel-Arab War, 1948-1949.; Jewish-Arab relations; Locusts -- Middle East; Medical care -- Palestine; Shipwrecks -- Atlantic Ocean; Swedes -- Palestine; Tourism -- Palestine; World War, 1914-1918 -- Palestine; Jerusalem -- History -- 19th century; Jerusalem -- History -- 20th century; Israel -- History; Jordan -- History; Palestine -- History -- 19th century; Palestine -- History -- 20th century; Turkey -- History -- Ottoman Empire, 1288-1918.